A general equilibrium analysis of the welfare impact of PROGRESA - Coady, David; Harris, Rebecca Lee (International Food Policy Research Institute, 2000)
The recently introduced PROGRESA program in Mexico can be interpreted as having multiple objectives, namely, (i) the alleviation of current poverty through the transfer of cash payments to poor households, and (ii) encouraging the accumulation of human capital by these households through the conditioning of these transfers on attendance at school and health centers. The latter can also be interpreted in terms of generating a sustained decrease in poverty over time. In this report we are concerned solely with the first objective. To date, the analysis of the welfare impact of these transfers has essentially been undertaken within a partial equilibrium framework which focuses exclusively on the direct effect of the transfers on the beneficiaries. In this report we emphasize the need to take a general equilibrium perspective of the program. In particular, we focus in on the indirect welfare effects which arise from the need to finance the program domestically. This focus is motivated by the belief that any credible poverty alleviation strategy must have underlying it a credible financing strategy.